Analysis of the effect of economic integration on the increase of gross domestic product in ASEAN countries - Ade Darmawan; Marselina, Marselina (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to explore the impact of the implementation of the ASEAN Economic Community (AEC) on the increase of Gross Domestic Product (GDP) in ASEAN member countries. The main focus of this study is on key variables including foreign direct investment, import-export ratio, labor productivity, and government debt. The AEC, which came into effect at the end of 2015, is expected to strengthen economic integration in the region by facilitating the flow of goods, services, and investment. The method used in this study is regression analysis to identify the relationship between these variables and GDP during the post-MEA period (2016-2022). The results of the analysis show that foreign direct investment and labor productivity have a significant positive influence on the increase of GDP in ASEAN countries. On the other hand, the import-export ratio shows a negative impact that needs to be watched closely, while government debt does not show a significant effect in this context. The findings provide important insights for policymakers in formulating more effective economic strategies to maximize the benefits of the AEC, as well as addressing the challenges posed by instability in trade ratios and debt management.